NUMBER OF PERIODIC SOLUTIONS OF CLASSES C2,4 AND C4,3 - Yasmin, Nusrat; Ashraf, Muhammad (Journal of Research (Science), 2003)
The classes C2,4 and C4,,3 of coefficients of one-dimensional nonautonomous differential equations are investigated for periodic solutions. Seven and Five periodic solutions are found for classes C2,4 and C4,3 respectively. The method we used is bifurcation of periodic solution from a fine - focus.